A refuge at Highland Hall [large type] - Turansky, Carrie (Edwardian brides, 2015)
"The Great War shakes the world of a spirited young woman and the brave British pilot she loves, taking her from London to her family's magnificent country estate, and sending him into the war-torn skies over France"--